Light and dissolved nutrients mediate recalcitrant organic matter decomposition via microbial priming in experimental streams. (20th March 2020) - Howard‐Parker, Brooke; White, Brendon; Halvorson, Halvor M.; Evans‐White, Michelle A.
Abstract: Environmental factors such as nutrient and light availability may play important roles in determining the magnitude and direction of microbial priming and detrital decomposition and, therefore, the relative importance of microbial priming in carbon (C) dynamics in freshwater ecosystems. We integrated light availability with an existing conceptual model predicting the magnitude of the priming effect (PE) along a dissolved nutrient gradient (i.e. nutrient PE model). Our modified light‐nutrient PE model hypothesises how light may mediate priming at any given nutrient concentration and provides a calculation method for quantitative PE values (i.e. light effect size at a given nutrient concentration). We used recirculating stream mesocosms with Quercus stellata (post oak) leaf litter as an organic matter (OM) substrate in a 150‐day experiment to test our model predictions. We manipulated light levels [ambient (full light), shaded ( c. 19% of ambient)] and phosphorus (P) concentration (10, 100, 500 µg PO4 ‐P/L) in a fully factorial design. We also supplied all mesocosms with 500 µg/L dissolved inorganic nitrogen. Microbial biomass, water column dissolved organic C, and leaf litter dry mass and recalcitrant OM [i.e. the fibre (cellulose + lignin) component of post oak substrate] were measured. Recalcitrant OM (ROM) k ‐rates (day −1 ) were used to calculate the light effect size within P treatments as a log response ratio ( ln [ambient k ‐rate/shade k ‐rate]) to ascertain PE magnitude and direction (positive or negative). Light was an important driver of dissolved organic C, a potential source of additional labile organic matter essential for priming heterotrophic microbes. There were weak PEs in total leaf litter dry mass remaining, but PEs were more pronounced in leaf litter ROM remaining. The strongest positive PEs (specific to litter ROM pools) occur in the highest P treatment, presumably due to a change in which nutrient, nitrogen versus P, was a limiting factor for microbes based on nutrient ratios rather than P concentration alone. These results illustrate the importance of considering light levels, nutrient ratios (rather than individual nutrients), and detrital ROM components in further PE model development.